2019
DOI: 10.4236/ae.2019.74009
|View full text |Cite
|
Sign up to set email alerts
|

Residual Spray for the Control of <i>Aedes</i> Vectors in Dengue Outbreak Residential Areas

Abstract: The incidence of dengue in Malaysia has shown an increasing trend since the year 2000. Vector control is the primary approach for dengue control in Malaysia. There is an urgent need for new or modified approaches such as the residual spraying on the outer walls that can potentially last long enough to control the Aedes population, particularly in the outbreak-prone areas. In this field study, we conducted outdoor residual spraying (ORS) using a newly formulated polymer-enhanced suspension concentrate (SC-PE) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…outdoor vector control strategies could be used for Aedes control in densely populated urban districts. As reported in other investigations (Lee et al, 2015;Hamid et al, 2019) and in agreement with our results, TORS or ADDs effectively reduced the mosquito population. It can, therefore, be expected that co-application of these techniques together with public cooperation would further enhance the vector control efficacy.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…outdoor vector control strategies could be used for Aedes control in densely populated urban districts. As reported in other investigations (Lee et al, 2015;Hamid et al, 2019) and in agreement with our results, TORS or ADDs effectively reduced the mosquito population. It can, therefore, be expected that co-application of these techniques together with public cooperation would further enhance the vector control efficacy.…”
Section: Discussionsupporting
confidence: 94%
“…K-Othrine Polyzone kills host-seeking and adult mosquitoes landing on the treated substrate, thereby lowering the number of adult mosquitoes in the area (Dunford et al ., 2018). Its use in TORS can potentially reduce the frequency of current insecticide applications for Aedes control due to its longer residual effect (Hamid et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Another study was later conducted using delta SC-PE 30 in the low-rise and high-rise residences. Bioassay results showed that the mortality percentage for Aedes was more than 80% for 16 weeks (Ab Hamid et al, 2019). Research in Tanzania using delta SC-PE showed to effectively cause 100% mortality in Blattella germanica for a period of 3 months even after exposure to sunlight, rainfall and daily temperature fluctuations (Kijlstra et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Parts of corridors with such objects are not sprayed. Based on our ndings on the residual effects of K-Othrine® Polyzone [17,21], TORS is conducted every four months in all intervention areas.…”
Section: Interventionsmentioning
confidence: 99%
“…Previous eld evaluation of TORS and ADDs showed effective reduction of the mosquito population [3,17]. In addition, the combination of insecticides with different modes of action in the same program is likely to limit insecticide resistance in the local Aedes vector population.…”
mentioning
confidence: 99%